If $\angle B$ and $\angle Q$ are acute angles such that $\sin B =\sin Q$, then prove that $\angle B =\angle Q$.
Let us consider two right triangles $ABC$ and $PQR$ where $\sin B=\sin Q$(see $Fig.$)
We have $\quad \sin B =\frac{A C}{A B}$
and $\sin Q =\frac{ PR }{ PQ }$
Then $\quad \frac{A C}{A B}=\frac{P R}{P Q}$
Therefore, $\frac{A C}{P R}=\frac{A B}{P Q}=k,$ say ...........$(1)$
Now, using Pythagoras theorem,
$BC =\sqrt{ AB ^{2}- AC ^{2}}$
and $QR =\sqrt{ PQ ^{2}- PR ^{2}}$
So, $\quad \frac{ BC }{ QR }=\frac{\sqrt{ AB ^{2}- AC ^{2}}}{\sqrt{ PQ ^{2}- PR ^{2}}}=\frac{\sqrt{k^{2} PQ ^{2}-k^{2} PR ^{2}}}{\sqrt{ PQ ^{2}- PR ^{2}}}=\frac{k \sqrt{ PQ ^{2}- PR ^{2}}}{\sqrt{ PQ ^{2}- PR ^{2}}}=k$ ..........$(2)$
From $( 1 )$ and $( 2 ),$ we have
$\frac{A C}{P R}=\frac{A B}{P Q}=\frac{B C}{Q R}$
Then,$\Delta ACB \sim \Delta PRQ$ and therefore, $\angle B =\angle Q$.
$(1+\tan \theta+\sec \theta)(1+\cot \theta-\operatorname{cosec} \theta)=..........$
Prove the following identities, where the angles involved are acute angles for which the expressions are defined.
$\frac{1+\sec A}{\sec A}=\frac{\sin ^{2} A}{1-\cos A}$
Evaluate:
$\frac{\tan 26^{\circ}}{\cot 64^{\circ}}$
In triangle $ABC ,$ right -angled at $B ,$ if $\tan A =\frac{1}{\sqrt{3}},$ find the value of:
$(i)$ $\sin A \cos C+\cos A \sin C$
$(ii)$ $\cos A \cos C-\sin A \sin C$
$\frac{2 \tan 30^{\circ}}{1-\tan ^{2} 30^{\circ}}=$